Phase I study of the anti-α5β1 monoclonal antibody MINT1526A with or without bevacizumab in patients with advanced solid tumors - Weekes, Colin D.; Rosen, Lee S.; Capasso, Anna; Wong, Kit Man; Ye, Weilan; Anderson, Maria; McCall, Bruce; Fredrickson, Jill; Wakshull, Eric; Eppler, Steve; Shon-Nguyen, Quyen; Desai, Rupal; et al. (Cancer chemotherapy and pharmacology, 2018)
Purpose MINT1526A is a monoclonal antibody that blocks the interaction of integrin alpha 5 beta 1 (α5β1) with its extracellular matrix ligands. This phase I study evaluated the safety and pharmacokinetics of MINT1526A with or without bevacizumab in patients with advanced solid tumors. Methods MINT1526A was administered every 3 weeks (Q3W) as monotherapy (arm 1) or in combination with bevacizumab 15 mg/kg, Q3W (arm 2). Each arm included a 3 + 3 dose-escalation stage and a dose-expansion stage. Results Twenty-four patients were enrolled in arm 1 (dose range 2–30 mg/kg) and 30 patients were enrolled in arm 2 (dose range 3–15 mg/kg). Monocyte α5β1 receptor occupancy was saturated at a dose of 15 mg/kg. No dose-limiting toxicities were observed, and the maximum tolerated dose was not reached in either arm. The most common adverse events, regardless of causality, included abdominal pain (25%), diarrhea (25%), nausea (21%), vomiting (21%), and fatigue (21%) in arm 1 and nausea (40%), fatigue (33%), vomiting (30%), dehydration (30%), headache (30%), and hypertension (30%) in arm 2. No grade ≥ 3 bleeding events were observed in either arm. No confirmed partial responses (PR) were observed in arm 1. In arm 2, one patient with thymic carcinoma experienced a confirmed PR and two patients with hepatocellular carcinoma (HCC) experienced durable minor radiographic responses. Conclusions MINT1526A, with or without bevacizumab, was well-tolerated. Preliminary evidence of combination efficacy, including in patients with HCC, was observed, but cannot be distinguished from bevacizumab monotherapy in this phase I study.